2023
DOI: 10.1097/aud.0000000000001398
|View full text |Cite
|
Sign up to set email alerts
|

The Self-Stigma of Hearing Loss in Adults and Older Adults: A Systematic Review

Abstract: Objectives: Previous studies have demonstrated that individuals with hearing loss can internalize social stigmas, resulting in several self-perceived negative connotations, such as incompetence, cognitive impairment, and social disability. This systematic review aimed to investigate the impact of the social stigma associated with hearing loss on the self-stigma experienced by adults and older adults. Design: Combinations of words and appropriate truncat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…One of the most devastating implications is that OTCs were intended to be an affordable introduction into receiving support for hearing loss. With BIPOC people already more likely to be living in a lower income bracket, OTCs could have been a better option to help mitigate the consequences of untreated hearing loss, such as dementia and social isolation [ 11 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the most devastating implications is that OTCs were intended to be an affordable introduction into receiving support for hearing loss. With BIPOC people already more likely to be living in a lower income bracket, OTCs could have been a better option to help mitigate the consequences of untreated hearing loss, such as dementia and social isolation [ 11 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…This design choice was made primarily due to the stigma associated with individuals wearing hearing aids being viewed as elderly or disabled. While the stigma has slowly become less prevalent in recent years, most users still prefer more discreet devices [ 11 , 12 , 13 , 14 ]. Having the option for hearing aid shells that blend into the user’s skin or hair color is an important consideration for hearing aid companies to consider when developing product colorways.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Psychosocial consequences of hearing loss are far-reaching and encompass various aspects of individuals’ lives. Research has shown that hearing loss is associated with social isolation and loneliness [e.g., ( 1 3 )], stigma [e.g., ( 4 , 5 )], anxiety and depression [e.g., ( 6 )], reduced family and community engagement [e.g., ( 7 )], and psychological distress [e.g., ( 8 )]. Negative psychosocial effects extend beyond the person with hearing loss.…”
Section: Introductionmentioning
confidence: 99%